(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Many mobile health applicationsincluding mobile heart monitoring applications are available on Apple App Store, and Google Play Store. However, when the user feels dissatisfied with the user interface design of the mobile heart monitoring application, it impacts user satisfaction level to the extent that the users do not use it anymore. User satisfaction level isa very important factor in usability to identify a mobile heart monitoring application whichis pleasant and comfortable forcontinuous use. This study recruited four cardiologists in a hospital in Palembang, Indonesia for evaluatingtheuser interface design ofa mobile heart monitoring prototype called HeartM. The prototype has several features including measuringpatient’s heart rate and blood pressurerate, treatment record, forum, and chat to ease communication between heart patients and their cardiologist. The focus of the user interface design evaluation are oncontent, visual and navigation aspects.This paper contributes to user interface design knowledge and design recommendations particularly for mobile heart monitoring applications.